Are there phylogenetic differences in salivary tannin‐binding proteins between browsers and grazers, and ruminants and hindgut fermenters?. Issue 19 (30th August 2020) - Ward, David; Schmitt, Melissa H.; Shrader, Adrian M.
Abstract: While feeding, mammalian browsers (primarily eat woody plants) encounter secondary metabolites such as tannins. Browsers may bind these tannins using salivary proteins, whereas mammalian grazers (primarily eat grasses that generally lack tannins) likely would not. Ruminant browsers rechew their food (ruminate) to increase the effectiveness of digestion, which may make them more effective at binding tannins than nonruminants. Few studies have included a sufficient number of species to consider possible scaling with body mass or phylogenetic effects on salivary proteins. Controlling for phylogeny, we ran inhibition radial diffusion assays of the saliva of 28 species of African herbivores that varied in size, feeding strategy, and digestive system. We could not detect the presence of salivary proline‐rich proteins that bind tannins in any of these species. However, using the inhibition radial diffusion assay, we found considerable abilities to cope with tannins in all species, albeit to varying degrees. We found no differences between browsers and grazers in the effectiveness of their salivary proteins to bind to and precipitate tannins, nor between ruminants and nonruminants, or scaling with body mass. Three species bound all tannins, but their feeding niches included one browser (gray duiker), one mixed feeder (bush pig), and one grazer (red hartebeest). Five closely related species of small ruminant browsers were very effective in binding tannins. Megaherbivores, considered generalists on account of their large body size, were capable of binding tannins. However, the grazing white rhinoceros was almost as effective at binding tannins as the megaherbivore browsers. We conclude, contrary to earlier predictions, that there were no differences in the relative salivary tannin‐binding capability that was related to common ancestry (phylogeny) or to differences in body size. Abstract : Mammalian browsers frequently encounter secondary metabolites such as tannins. Browsers may bind these tannins using salivary proteins, while mammalian grazers likely would not. Controlling for phylogeny, we ran inhibition radial diffusion assays of the saliva of 28 species of African herbivores (browsers, grazers, ruminants, and nonruminants) that differed considerably in size. We conclude, contrary to earlier predictions, that there were no differences in the relative salivary tannin‐binding capability of browsers and grazers, nor ruminants versus nonruminants, that were related to common ancestry (phylogeny) or to differences in body size.